Handbook of Nanosafety : Measurement, Exposure and Toxicology. - Vogel, Ulla (Gama Network Series., 2013)
Handbook of Nanosafety: Measurement, Exposure and Toxicology, written by leading international experts in nanosafety, provides a comprehensive understanding of engineered nanomaterials (ENM), current international nanosafety regulation, and how ENM can be safely handled in the workplace. Increasingly, the importance of safety needs to be considered when promoting the use of novel technologies like ENM. With its use of case studies and exposure scenarios, Handbook of Nanosafety demonstrates techniques to assess exposure and risks and how these assessments can be applied.